Emergency management : the American experience, 1900-2010 - Rubin, Claire B. (Online access with subscription: Proquest Ebook Central., 2012)
Following in the footsteps of its popular predecessor, the second edition of Emergency Management: The American Experience 1900--2010 provides the background needed to understand the key political and policy underpinnings of emergency management, exploring how major "focusing events" have shaped the development of emergency management. It builds on the original theoretical framework and chronological approach, but improves on the first edition by adding fresh information on older events such as Hurricane Katrina as well as a new chapter covering the BP oil spill in 2010 and the unpre